2022
DOI: 10.1002/hsr2.794
|View full text |Cite
|
Sign up to set email alerts
|

Standardized reporting of amnion and amnion/chorion allograft data for wound care

Abstract: Background: The favorable biological and mechanical properties of the most common components of the placenta, the amnion and chorion, have been exploredfor regenerative medical indications. The use of the combination of amnion and chorion has also become very popular. But, published data from placental tissues in their final, useable form is lacking. During treatment with membrane product, the tissue is usually sterile, intact and laid on a wound or treatment area. The factors available to the treatment area f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
11
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(11 citation statements)
references
References 79 publications
(140 reference statements)
0
11
0
Order By: Relevance
“…The umbilical amnion has superior tensile strength due to a collagen-rich, thickened compact stromal layer. 29,30 Slentz DH, et al 2 reported the novel use of cryopreserved ultra-thick human amniotic membrane in three patients retrospectively with anophthalmia secondary to enucleation for blind painful eye (n = 2) and congenital anophthalmia (n = 1). An average follow-up duration of 12.3 months.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The umbilical amnion has superior tensile strength due to a collagen-rich, thickened compact stromal layer. 29,30 Slentz DH, et al 2 reported the novel use of cryopreserved ultra-thick human amniotic membrane in three patients retrospectively with anophthalmia secondary to enucleation for blind painful eye (n = 2) and congenital anophthalmia (n = 1). An average follow-up duration of 12.3 months.…”
Section: Discussionmentioning
confidence: 99%
“…The umbilical amnion has superior tensile strength due to a collagen-rich, thickened compact stromal layer. 29,30…”
Section: Discussionmentioning
confidence: 99%
“…ECM proteins in their normal biological structures within intact tissues are known to stimulate and regulate cellular proliferation, migration, and differentiation through a number of mechanisms; therefore, the maintenance of the native ECM within a biological tissue is expected to exhibit greater responses than those whose ECM has been disrupted [23,26]. HSCM maintained ECM and key regulatory proteins that are characteristically present in unprocessed chorion membranes [17]. The distribution of ECM proteins and growth factors throughout HSCM was comparable to donor-matched unprocessed tissues.…”
Section: Discussionmentioning
confidence: 99%
“…While placental membranes as a whole have been widely studied and used clinically, there are limited studies evaluating the potential benefits of the chorion membrane independently. The chorion membrane, comprising the reticular, basement membrane, and trophoblast layers, is thicker than the amnion membrane with a robust ECM and has been reported to be a significant contributor of growth factors and cytokines, including tissue inhibitors of metalloproteases (TIMPs), which inhibit matrix metalloproteases (MMPs) [15,17,18]. While the balance of MMPs and TIMPs is known to be important for regulating collagen deposition, aberrant or prolonged expression of MMPs is known to be a major factor in non-healing and chronic wounds [19,20].…”
Section: Introductionmentioning
confidence: 99%
“…These critical factors include a precise description of the PnD used and adequate information on the in vitro tests used to characterize PnD. A recent study by Sabol et al (2022) , reported that published data from placental tissues in their final, useable form is lacking. In their study they highlighted the need for standardized data collection and reporting in the field of dry membrane allografts.…”
Section: Introductionmentioning
confidence: 99%